Study and Application of Adaptive Micro-brake Technology When MetrosPassing No-electricity Areas - XU Shao-long; NI Da-cheng; LIU Liang-Jie; WANG Yong-tong; ZHENG Liang-guang (机车电传动)
Power interruption and intermediate DC link voltage variation were analyzed in detail when metros passing no-electricity areas, and adaptive micro-brake technique for keeping the intermediate DC voltage steady were put forward. Corresponding application solutions was provided, effectivity and practicability of which was validated by experimental verification. The experimental results showed that the adaptive micro-brake technique met the requirements of domestic and foreign customers, and reached advanced level in the same industry.